Mapping an extended metabolic profile of gliomas using high-resolution P-31 MRSI at 7T - Korzowski, Andreas; Weckesser, Nina; Franke, Vanessa; Breitling, Johannes; Görke, Steffen; Schlemmer, Heinz-Peter; Ladd, Mark E.; Bachert, Peter; Paech, Daniel (Frontiers in neurology, 2021)
Phosphorus magnetic resonance spectroscopic imaging (P-31 MRSI) is of particular interest for investigations of patients with brain tumors as it enables to non-invasively assess altered energy and phospholipid metabolism in vivo. However, the limited sensitivity of P-31 MRSI hampers its broader application at clinical field strengths. This study aimed to identify the additional value of P-31 MRSI in patients with glioma at ultra-high B-0 = 7T, where the increase in signal-to-noise ratio may foster its applicability for clinical research. High-quality, 3D P-31 MRSI datasets with an effective voxel size of 5.7 ml were acquired from the brains of seven patients with newly diagnosed glioma. An optimized quantification model was implemented to reliably extract an extended metabolic profile, including low-concentrated metabolites such as extracellular inorganic phosphate, nicotinamide adenine dinucleotide [NAD(H)], and uridine diphosphoglucose (UDPG), which may act as novel tumor markers; a background signal was extracted as well, which affected measures of phosphomonoesters beneficially. Application of this model to the MRSI datasets yielded high-resolution maps of 12 different P-31 metabolites, showing clear metabolic differences between white matter (WM) and gray matter, and between healthy and tumor tissues. Moreover, differences between tumor compartments in patients with high-grade glioma (HGG), i.e., gadolinium contrast-enhancing/necrotic regions (C+N) and peritumoral edema, could also be suggested from these maps. In the group of patients with HGG, the most significant changes in metabolite intensities were observed in C+N compared to WM, i.e., for phosphocholine +340%, UDPG +54%, glycerophosphoethanolamine -45%, and adenosine-5 '-triphosphate -29%. Furthermore, a prominent signal from mobile phospholipids appeared in C+N. In the group of patients with low-grade glioma, only the NAD(H) intensity changed significantly by -28% in the tumor compared to WM. Besides the potential of P-31 MRSI at 7T to provide novel insights into the biochemistry of gliomas in vivo, the attainable spatial resolutions improve the interpretability of P-31 metabolite intensities obtained from malignant tissues, particularly when only subtle differences compared to healthy tissues are expected. In conclusion, this pilot study demonstrates that P-31 MRSI at 7T has potential value for the clinical research of glioma.
Gesehen am 04.02.2022